FOBO in Gen Z from an Islamic Economic Perspective: Implications for Consumption and Investment - Misi Anggraini (Journal of Islamic Economics and Finance Studies, 2026)
This study examined the phenomenon of FOBO (Fear of Better Options) among Generation Z from the perspective of Islamic economics, focusing on its implications for consumption and investment behavior. The method used was qualitative with a case study approach. Data were collected through in-depth interviews with 25 purposively selected Generation Z informants who were active in economic activities in Indonesia. Thematic analysis was conducted using NVivo 12 software. The research results showed that FOBO significantly influenced the decision-making of Generation Z, causing hesitation and delays in commitment in consumption and investment. This behavioral pattern challenged the principles of Islamic economics related to wise financial management and ethical investment. The study discussed the impact of FOBO on financial decisions and provided recommendations for aligning Generation Z's economic behavior with Islamic values. The findings enriched the understanding of modern economic behavior within the Sharia framework and served as a basis for further research on financial literacy and consumer ethics among young Muslim generations.